Ureterorenoscopy with Stenting and Its Effect on Female Sexual Function - Akdeniz, Ekrem; Bolat, Mustafa Suat (Urology Journal, 2017)
Purpose: Various etiological factors have been studied which negatively affect female sexual function, but the effects of ureteroscopic stone surgery on women’s sexual dysfunction remain unknown. The aim of this study was to investigate the effect of ureteroscopic stone surgery with postoperative stenting on female sexual function. Materials and Methods: This study included 30 sexually active female patients who underwent ureteroscopic stone surgery with JJ stenting (study group) and 26 age-matched female patients with ureteral stone surgery without JJ stenting (control group). Sexual function was assessed at preoperative and at the first and 3rd months postoperative using the Female Sexual Function Index. Overall satisfaction in relation to the age, operation time, presence of stents, body mass index, educational status, previous operations, income status, and psychogenic status was evaluated. Results: Sexual function was adversely affected by ureteroscopic stone surgery with JJ stenting; but psychogenic, educational and income status remained stable. Mean individual female sexual function subscores were statistically significant between the study and control groups, but the differences in the mean Beck scores minimally improved between the two groups at preoperative (p = 0.19) visit, whereas first month (p = 0.08) and third month (p = 0.31) of postoperative controls were deteriorated but the differences were not statistically significant, respectively. Conclusion: Ureterorenoscopy with JJ stenting has considerably negative effects on female sexual function. JJ stenting causes temporary sexual deterioration in women and it generally ceases at the end of the 3rd month after ureteroscopic surgery. Therefore, JJ stenting should be avoided or used for as short a time as possible. If JJ stenting is inevitable, patients should be warned about a temporary decline in their sexual function during the first month of the operation that resolves at most in three months.